IMPROVEMENT POSSIBILITIES FOR THE METHOD OF VALUE STREAM MAPPING - Szentesi, Szabolcs; Tamás, Péter; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2016)
The coordinated development of the production processes in logistics systems is a decisive competitive factor, because it can significantly reduce logistics costs and/or improve the level of services. The value stream mapping method used in the lean philosophy can be very efficient when it comes to the development of logistics processes of distinct product families. In the case of simultaneous production of multiple product families using material flow processes, that intersect each other, as well as the processes are characterized by significant randomness (eg.: machinery and material handling equipment failure etc.), then the process improvement methods cannot be used very effectively in practice. Of course, there are many attempts to develop logistics processes in intermitted manufacturing systems, which are discussed in detail in the literature review. For better understanding we present the value stream mapping method through an example. Then we give a little insight into the new opportunities of process development, which is the combination of value-stream mapping with simulation modeling. This new trend provides opportunity to perform wider range of process development tasks. The detailed elaboration of this new area requires several research tasks to perform, which are presented schematically in this article.